RETRACTED ARTICLE: The JAK2/STAT3 and mitochondrial pathways are essential for quercetin nanoliposome-induced C6 glioma cell death - G Wang; J J Wang; X L Chen; S M Du; D S Li; Z J Pei; H Lan; L B Wu (Cell Death and Disease)
Abstract The formulation of quercetin nanoliposomes (QUE-NLs) has been shown to enhance QUE antitumor activity in C6 glioma cells. At high concentrations, QUE-NLs induce necrotic cell death. In this study, we probed the molecular mechanisms of QUE-NL-induced C6 glioma cell death and examined whether QUE-NL-induced programmed cell death involved Bcl-2 family and mitochondrial pathway through STAT3 signal transduction pathway. Downregulation of Bcl-2 and the overexpression of Bax by QUE-NL supported the involvement of Bcl-2 family proteins upstream of C6 glioma cell death. In addition, the activation of JAK2 and STAT3 were altered following exposure to QUE-NLs in C6 glioma cells, suggesting that QUE-NLs downregulated Bcl-2 mRNAs expression and enhanced the expression of mitochondrial mRNAs through STAT3-mediated signaling pathways either via direct or indirect mechanisms. There are several components such as ROS, mitochondrial, and Bcl-2 family shared by the necrotic and apoptotic pathways. Our studies indicate that the signaling cross point of the mitochondrial pathway and the JAK2/STAT3 signaling pathway in C6 glioma cell death is modulated by QUE-NLs. In conclusion, regulation of JAK2/STAT3 and ROS-mediated mitochondrial pathway agonists alone or in combination with treatment by QUE-NLs could be a more effective method of treating chemical-resistant glioma.